Analisis perbandingan fama & french three factor model dan fama & french five factor model dalam menjelaskan expected return portofolio - Mariyah Al Qibthiyyah; Wiwit Hariyanto (Jurnal Ekonomi, Bisnis dan Pendidikan (JEBP), 2022)
Abstract Mariyah, Al Qibthiyyah. 2022. This study aims to determine the development of a portfolio by Fama French Three Factor Model and Fama French Five Factor Model in addition to examining whether there are differences between the method of Fama French Three Factor Model and Fama French Five Factor Model in explaining expected returns portfolio. This research used a quantitative method to prove the research hypothesis. The population of this study was all stocks listed in the LQ-45 Index from 2017 through 2018. The sample selection technique in this study used a purposive sampling method to acquire 35 companies that were used as research samples. The methods used in this research were paired samples t-test and Kolmogrov-Smirnov test. The examination was done using the PASW SPSS 18 program. Based on the results of the study using the Fama French Three Factor Model method, 16 stocks have a positive expected return value. There are ASII, BBCA, BBNI, BBTN, EXCL, GGRM, HMSP, ICBP, INTP, JSMR, KLBF, SMGR, SRIL, UNTR, UNVR with an average expected return of 0,0800344. Meanwhile, 12 stocks have a positive expected return value as the study results using the Fama French Five Factor Model method. There are ANTM, ASII, BBCA, BBNI, BBTN, BMRI, GGRM, INTP, KLBF, SMGR, SRIL, and UNTR with an average expected return of 0,1143472. The diverse test results in this study indicate that there is no significant difference between the Fama French Three Factor Model and the Fama French Five Factor Model in explaining the expected return portfolio. Abstrak Mariyah, Al Qibthiyyah.2022. Penelitian ini bertujuan untuk mengetahui pembentukan portofolio dengan metode Fama French Three Factor Model dan Fama French Five Factor Model serta menguji apakah terdapat perbedaan antara metode Fama French Three Factor Model dan Fama French Five Factor Model dalam menjelaskan expected return portofolio. Penelitian ini menggunakan metode kuantitatif untuk membuktikan hipotesis penelitian. Populasi penelitian ini adalah seluruh saham yang terdaftar dalam Indeks LQ-45 periode 2017-2018. Teknik pemilihan sampel dalam penelitian ini menggunakan metode purposive sampling sehingga diperoleh 35 perusahaan yang dijadikan sampel penelitian. Metode yang digunakan dalam penelitian ini adalah uji paired sample t-test dan uji kolmogrov-smirnov. Pengujian dilakukan dengan menggunakan program PASW SPSS 18. Berdasarkan hasil penelitian menggunakan metode Fama French Three Factor Model terdapat 16 saham yang memiliki expected return positif yaitu ASII, BBCA, BBNI, BBTN, EXCL, GGRM, HMSP, ICBP, INTP, JSMR, KLBF, SMGR, SRIL, UNTR, UNVR dengan rata-rata expected return sebesar 0,0800344. Sedangkan dalam metode Fama French Five Factor Model terdapat 12 saham yang memiliki nilai expected return positif yaitu, ANTM, ASII, BBCA, BBNI, BBTN, BMRI, GGRM, INTP, KLBF, SMGR, SRIL, UNTR dengan rata-rata expected return sebesar 0,1143472. Hasil uji beda dalam penelitian ini menunjukkan bahwa tidak terdapat perbedaan yang signifikan antara Fama French Three Factor Model dan Fama French Five Factor Model dalam menjelaskan expected return portofolio.